The gender and media reader - Kearney, Mary Celeste, 1962- (New York : Routledge, 2012)
This book is an essential text for those interested in gender and media studies, its primary topics, debates, and theoretical approaches. The primary objective of this collection is to expand readers' knowledge of how gender operates within media culture through engagement with foundational writings as well as more contemporary research in this field. Taking a multiperspectival approach that considers gender broadly and examines media texts alongside their production and consumption, The Gender and Media Reader enables readers' critical thinking about how gender is constructed, contested, and subverted in different sites within media culture. Along with the main introduction, individual section introductions facilitate readers' understanding of the development of gender and media studies by contextualizing the various topics, debates, and theoretical approaches that have shaped it, as well as by highlighting current trends. --from back cover.
Includes bibliographical references and index.
Keywords: Mass media and sex; Sex role in mass media; Mass media and culture